PHP 8 revealed : use attributes, the JIT compiler, union types, and more for web development - Engebreth, Gunnard (Apress, 2021)
Discover the new and updated features of PHP 8, such as the JIT compiler, union types, and attributes, with code examples of each. For each feature, the author includes real-life cases for its use and explains its benefits. What You Will Learn Utilize the new features of PHP 8 and modern development technologies Work with the JIT compiler in PHP 8 Discover PHP 8 using real-life cases Increase your available resources to become more valuable in your development team Who This Book Is For Experienced PHP programmers new to PHP 8.